2022
DOI: 10.3389/fcvm.2022.969325
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based time discrepancy in diagnosis of coronary artery disease based on data analytics of electronic medical records

Abstract: BackgroundWomen continue to have worse Coronary Artery Disease (CAD) outcomes than men. The causes of this discrepancy have yet to be fully elucidated. The main objective of this study is to detect gender discrepancies in the diagnosis and treatment of CAD.MethodsWe used data analytics to risk stratify ~32,000 patients with CAD of the total 960,129 patients treated at the UCSF Medical Center over an 8 year period. We implemented a multidimensional data analytics framework to trace patients from admission throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Several reasons have been reported in the literature to fully or at least partially explain a possible worse outcome of female gender after CABG. First, it is reported that there is a difference from the first time of admission to diagnostic cardiac catheterization in female gender in comparison with men, which may account, given the delay observed, for the more severe urgent or emergent clinical presentation at the time of CABG surgery, consequently increasing the operative risk in women ( 8 ). Secondly, the progression of the atherosclerotic disease most likely occurs in women at the end of childbearing age, i.e., when the protective estrogenic effect is less and therefore as compared with men, women arrive at the observation with more advanced age, which “ per se ” represents one of the most important predictors of worse in-hospital outcome ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reasons have been reported in the literature to fully or at least partially explain a possible worse outcome of female gender after CABG. First, it is reported that there is a difference from the first time of admission to diagnostic cardiac catheterization in female gender in comparison with men, which may account, given the delay observed, for the more severe urgent or emergent clinical presentation at the time of CABG surgery, consequently increasing the operative risk in women ( 8 ). Secondly, the progression of the atherosclerotic disease most likely occurs in women at the end of childbearing age, i.e., when the protective estrogenic effect is less and therefore as compared with men, women arrive at the observation with more advanced age, which “ per se ” represents one of the most important predictors of worse in-hospital outcome ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons may have contributed to similar operative results in our study. Panahiazar et al ( 8 ) reported that, as compared with men, women had an extra 127 days delay between angiographic diagnosis and coronary artery bypass graft. Being a referral center for CABG surgery, it is possible that there was no delay in the clinical diagnosis and surgical treatment in women in comparison with men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ML in clinical decision making can provide a more comprehensive analysis of all available data on patients suspected of CAD, which may be difficult for physicians to do objectively [66][67][68][69]. Cardiologists have to integrate several data sources, including clinical data, CT imaging, and SPECT stress testing, among others, to make clinical decisions, but there is no consistent method for integrating all of this information [70][71][72]. Additionally, guidelines recommend including certain variables in the myocardial perfusion imaging (MPI) report, but there is currently no standardized way to include them in the report [73].…”
Section: Plos Onementioning
confidence: 99%